2017
DOI: 10.1080/14767058.2017.1288208
|View full text |Cite
|
Sign up to set email alerts
|

When should repeat cesarean delivery be scheduled, after two or more previous cesarean deliveries?

Abstract: Planned CD at 39 weeks, rather than at 38 weeks, is associated with more unscheduled CDs, a similar rate of maternal and neonatal composite morbidity, but a decreased rate of neonatal respiratory morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The association of URCD with untoward maternal outcome observed in our study was concordant with the findings of other studies, 8,9,12–14,28 although some investigations did not identify a similar association, despite detecting higher rates of URCD 29–31 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The association of URCD with untoward maternal outcome observed in our study was concordant with the findings of other studies, 8,9,12–14,28 although some investigations did not identify a similar association, despite detecting higher rates of URCD 29–31 …”
Section: Discussionsupporting
confidence: 92%
“…The association of URCD with untoward maternal outcome observed in our study was concordant with the findings of other studies, 8,9,[12][13][14]28 although some inves- tigations did not identify a similar association, despite detecting higher rates of URCD. [29][30][31] Interestingly, adverse maternal outcome encountered following URCD was not influenced by gestational age; performing URCD at early-term or at term was consistently associated with untoward maternal outcome, and was not improved by delivery at 39 WG. Similar observations have been made in other studies; 12,32 however our results are inconsistent with the conclusions of Spong et al who hypothesized that early delivery before the development of lower uterine segment, together with adhesions were responsible for increased intraoperative blood loss and prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 96%
“…Our results were similar, but the number of patients with four or more previous CSs was not explicitly stated in that prior work. The same study added that the number of previous CSs was not associated with adverse neonatal outcomes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Still another study compared repeat cesarean deliveries at 38 and 39 weeks; they found that neonatal respiratory morbidity decreased at 39 weeks versus 38 weeks, and there was no change in maternal complications between these groups [17]. Although the rate of unscheduled CS at 39 weeks was higher than that at 38 weeks, the authors recommended elective timing at 39 weeks regardless of the number of previous cesarean sections due to neonatal benefits.…”
Section: Discussionmentioning
confidence: 99%
“…After 38 completed weeks of pregnancy, elective caesarean sections are generally associated with a lower incidence of immediate respiratory problems in term newborns (1). Kadour et al reported that neonates born by elective caesarean section at 38 weeks gestation had a nearly 3-fold higher rate of neonatal respiratory morbidity then neonates born at 39 weeks gestation (5.8% vs. 2.1%) (2). For this reason, recommendations for performing an elective caesarean section after 38 completed weeks of pregnancy have been integrated into the guidelines of the most respectable societies that are followed not only in the countries of origin where the societies operate, but also worldwide (3).…”
Section: Introductionmentioning
confidence: 99%